2018
DOI: 10.1111/ejh.13173
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of sickle erythrocytes in patients with sickle‐cell anemia: The effect of hydroxyurea, fetal hemoglobin, and α‐thalassemia

Abstract: Elevated levels of HbF with or without HU and α-thalassemia improve sickle RBC rheology, which, in turn, improve the clinical picture of SCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…At the same time, the blood of patients with rare anemias was investigated ( Clark et al, 1980 ), and as the Technicon ektacytometers were replaced by the second generation Lorrca MaxSis devices produced by RR Mechatronics, scrupulous comparison of the readouts obtained by both types of devices was performed for blood of patients with hereditary hemolytic anemia. ( Da Costa et al, 2016 ; Lazarova et al, 2017 ; Ballas et al, 2018 ; Ciepiela, 2018 ; Llaudet-Planas et al, 2018 ; Zaninoni et al, 2018 ; Kaestner and Bianchi, 2020 ; Zaidi et al, 2020 ; Zama et al, 2020 ). The number of reports on the clinical applications of the device for the assessment of the changes in rheology for human patients is steadily growing.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the blood of patients with rare anemias was investigated ( Clark et al, 1980 ), and as the Technicon ektacytometers were replaced by the second generation Lorrca MaxSis devices produced by RR Mechatronics, scrupulous comparison of the readouts obtained by both types of devices was performed for blood of patients with hereditary hemolytic anemia. ( Da Costa et al, 2016 ; Lazarova et al, 2017 ; Ballas et al, 2018 ; Ciepiela, 2018 ; Llaudet-Planas et al, 2018 ; Zaninoni et al, 2018 ; Kaestner and Bianchi, 2020 ; Zaidi et al, 2020 ; Zama et al, 2020 ). The number of reports on the clinical applications of the device for the assessment of the changes in rheology for human patients is steadily growing.…”
Section: Introductionmentioning
confidence: 99%
“…and probably 0% in the study of Embury et al 8 . We recently showed that patients with fetal Hb (HbF) level of >10% and without α‐thalassaemia had greater RBC deformability than patients with α‐thalassaemia and a HbF level of <10% 13 . Indeed, promoting HbF production through HU therapy in ˜75% of the patients of the present study could have lowered the effects of α‐thalassaemia, although α‐thalassaemia may also influence the HbF level 3 and could explain the discrepancies.…”
Section: Discussionmentioning
confidence: 93%
“…41,42 It also improves RBC deformability. 43 More recently, HU was reported to have antioxidant activity. 44 It appears that patients whose high neutrophil and reticulocyte counts decrease significantly after HU therapy have a higher increase in Hb F levels.…”
Section: Company Mechanism Of Action Indicationmentioning
confidence: 99%